2022
DOI: 10.1038/s41467-022-28516-0
|View full text |Cite
|
Sign up to set email alerts
|

Facet-dependent electrooxidation of propylene into propylene oxide over Ag3PO4 crystals

Abstract: The electrooxidation of propylene into propylene oxide under ambient conditions represents an attractive approach toward propylene oxide. However, this process suffers from a low yield rate over reported electrocatalysts. In this work, we develop an efficient electrocatalyst of Ag3PO4 for the electrooxidation of propylene into propylene oxide. The Ag3PO4 cubes with (100) facets exhibit the highest yield rate of 5.3 gPO m−2 h−1 at 2.4 V versus reversible hydrogen electrode, which is 1.6 and 2.5 times higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…The faraday efficiency (FE) of ZnCo-ZIF-C3 (>85% at relatively low current density) is also the highest among all samples (Figure e), indicating remarkable H 2 O 2 selectivity. The decrease of FE at higher current density may be attributed to the competing H 2 O 2 reduction reaction (H 2 O 2 RR) process . The cumulative H 2 O 2 yield of ZnCo-ZIF-C3 increases linearly within 2 h continuous test, indicating constant production of H 2 O 2 (Figure f).…”
Section: Resultsmentioning
confidence: 99%
“…The faraday efficiency (FE) of ZnCo-ZIF-C3 (>85% at relatively low current density) is also the highest among all samples (Figure e), indicating remarkable H 2 O 2 selectivity. The decrease of FE at higher current density may be attributed to the competing H 2 O 2 reduction reaction (H 2 O 2 RR) process . The cumulative H 2 O 2 yield of ZnCo-ZIF-C3 increases linearly within 2 h continuous test, indicating constant production of H 2 O 2 (Figure f).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the AgPz, the hydrogen bond between the pyrrolic N–H and OH for AgPz-H vac was broken, resulting in the weaker E B (*OH) of −2.75 eV. It has been reported that strong E B (*OH) favored the dissociation of H 2 O into *OH, whereas the weak E B (*OH) was beneficial to the coupling of *OH and propylene. In this way, the dynamically reversible interconversion between AgPz and AgPz-H vac was considered to facilitate the dissociation of H 2 O into *OH and the transfer of *OH to propylene simultaneously. We conducted the ab initio molecular dynamics calculations for each elementary step involved in the electrooxidation of propylene into PG over AgPz and AgPz-CH 3 with the solvent effect (Figure S18).…”
Section: Resultsmentioning
confidence: 99%
“…18,19 The strong E B (*OH) favors the dissociation of H 2 O into *OH, whereas the transfer of *OH to propylene would be impeded. 19,20 On the contrary, the weak E B (*OH) is beneficial to the combination of *OH and propylene but detrimental for *OH generation. 21,22 As such, the catalytic performance for propylene electrooxidation would be restricted due to the scaling relationship of the E B (*OH) over the conventional catalysts.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propene is an important feedstock (over 130 million tons of capacity) for manufacturing numerous commodity chemicals in the industry. Traditionally, propene conversion is via thermocatalysis. With the dramatic increase in available renewable electricity in recent years, directly converting propene via electrochemical approaches under moderate conditions becomes a capable alternative. As an anodic reaction, propene oxidation may replace the oxygen evolution reaction in electrolyzers to couple with cathodic hydrogen evolution or the CO 2 reduction reaction. The lower working potential of propene oxidation than the OER and high value-added products rather than O 2 can greatly benefit the energy efficiency and economic effectiveness of the electrolyzers .…”
Section: Introductionmentioning
confidence: 99%